2017
DOI: 10.7759/cureus.1690
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumor of the Patellar Tendon Sheath: A Rare Case of Anterior Knee Pain

Abstract: Giant cell tumor of the tendon sheath (GCTTS) is a benign, proliferative lesion of the synovium of the joint, the bursa, and the tendon sheath. We report a case of intra-articular, localized GCTTS arising from the patellar tendon, which is a rare cause of anterior knee pain. The diagnosis may be delayed due to non-specific symptoms and normal plain radiographic findings. Magnetic resonance imaging (MRI) is diagnostic to detect the lesion, but several other clinical entities and lesions should be evaluated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 9 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The presence of TGCT in Hoffa's fat pad is a very rare finding [4]. TGCT is usually seen in the age group of 30 to 50 years and more commonly in women, and our patient was a 33-year-old woman [1].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The presence of TGCT in Hoffa's fat pad is a very rare finding [4]. TGCT is usually seen in the age group of 30 to 50 years and more commonly in women, and our patient was a 33-year-old woman [1].…”
Section: Discussionmentioning
confidence: 67%
“…Due to nonspecific signs and symptoms, diagnosis of a giant cell tumor can be delayed for weeks or months. The common concerns may include painless or painful palpable swelling, joint effusion, locking of the knee joint, and restriction of movement [1,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Residual tumors are the main cause of recurrence. Therefore, Kilicaslan et al [9] reported that they were more inclined to open surgery to remove the lesion without leaving any residue tissue. However, I recommend arthroscopic resection, because during the arthroscopic operation the image is enlarged, the removal is more comprehensive, with a small trauma and is easy to recover after surgery.…”
Section: Discussionmentioning
confidence: 99%